Experiences of termination of pregnancy for a fetal anomaly: A qualitative study of virtual community messages. (October 2016) - Carlsson, Tommy; Bergman, Gunnar; Karlsson, Anna-Malin; Wadensten, Barbro; Mattsson, Elisabet
Abstract: Objective: to explore experiences described by posters in Swedish virtual communities before, during and after termination of pregnancy due to a fetal anomaly. Design: cross-sectional qualitative study of messages in virtual communities. The messages were purposefully selected in 2014 and analyzed with inductive qualitative manifest content analysis. Setting: two large and active Swedish virtual communities. Sample: 1623 messages from 122 posters (112 females, 1 male, and 9 did not disclose their sex), written between 2008 and 2014. The majority of the posters were females (91%) with recent experience of termination of pregnancy following different prenatal diagnoses (63% less than one year since the termination). Measurements and findings: before the termination, posters experienced an emotional shock and a difficult decision. During the termination, they needed compassionate care from present caregivers, experienced intense emotional and physical pain, lacked an understanding about the abortion, and expressed varied feelings about the option to view the fetus. After the termination, posters used different strategies to come to terms with and accept the decision, experienced a perinatal loss, expressed fears of recurrence, and longed for a new child. Key conclusions: spanning across the time before, during and after the abortion, women who terminate a pregnancy due to a fetal anomaly express considerable physical and emotional pain, with psychosocial and reproductive consequences. Implications for practice: information and preparation, including the decision whether or not to view the fetus, are important aspects to consider when caring for individuals who have decided to terminate a pregnancy for a fetal anomaly. The findings indicate a need for structures that offer support to women who suffer from fears of recurrence in future pregnancies.